2018
DOI: 10.1016/j.dyepig.2018.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Cell penetrating, mitochondria targeting multiply charged DABCO-cyanine dyes

Abstract: Unless otherwise stated, all starting materials and solvents required for the synthesis of the DABCO cyanine dyes were purchased from Sigma-Aldrich, Organica Feinchemie GmbH Wolfen, Fluka, Alfa-Aesar, TCI Europe, Deutero GmbH, and used without any further purification. The solvents used for the spectroscopic analyses were purchased form Macron Fine Chemicals TM. All other starting materials and solvents were commercial products of analytical grade and were used without further purification. 2.2 Synthesis and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…The colocalization experiments using organelle-selective fluorescent probes revealed that the emission in the cytoplasm was due to the accumulation of BIQ in the mitochondria (Figure S11). Such a behavior was reported in other monomethine cyanines. , On the other hand, it is highly likely that the nucleolar fluorescence signal arises from the binding of BIQ to RNAs that were abundant in the nucleolus, such as rRNAs. To confirm this, we examined deoxyribonuclease (DNase) and ribonuclease (RNase) digestion experiments in fixed-permeabilized MCF7 cells (Figure B). As observed for the living cells (cf.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…The colocalization experiments using organelle-selective fluorescent probes revealed that the emission in the cytoplasm was due to the accumulation of BIQ in the mitochondria (Figure S11). Such a behavior was reported in other monomethine cyanines. , On the other hand, it is highly likely that the nucleolar fluorescence signal arises from the binding of BIQ to RNAs that were abundant in the nucleolus, such as rRNAs. To confirm this, we examined deoxyribonuclease (DNase) and ribonuclease (RNase) digestion experiments in fixed-permeabilized MCF7 cells (Figure B). As observed for the living cells (cf.…”
Section: Resultsmentioning
confidence: 53%
“…Such a behavior was reported in other monomethine cyanines. 36,37 On the other hand, it is highly likely that the nucleolar fluorescence signal arises from the binding of BIQ to RNAs that were abundant in the nucleolus, such as rRNAs. 13−16 To confirm this, we examined deoxyribonuclease (DNase) and ribonuclease (RNase) digestion experiments in fixed-permeabilized MCF7 cells (Figure 2B).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…N-Methyl-1,4-diazabicyclo[2.2.2]octan-1-ium (MDABCO) iodide was synthesized as described elsewhere. 44,45 Metal halide perovskite films were obtained by using the antisolvent method described elsewhere. 46,47 N-Methyl-1,4-diazabicyclo[2.2.2]octan-1-ium Ammonium Iodide (MDNI).…”
Section: ■ Conclusionmentioning
confidence: 99%
“… 6 Similar behavior was also found in the parent BIQ 4 and other monomethine cyanines. 7 Meanwhile, it is highly likely that the fluorescence signal in the nucleolus arises from the binding of BIQ–NH 2 to RNAs that were abundant in the nucleolus, such as ribosomal RNAs (rRNAs). 3,4 This was supported by the examination of nuclease digestion in the fixed-permeabilized cells ( Fig.…”
mentioning
confidence: 99%